Autologous Osteochondral Grafts for Knee Osteochondral Diseases Result in Good Patient-Reported Outcomes in Patients Older Than 60 Years - Yasuaki Nakagawa, M.D.; Shogo Mukai, M.D.; Kentaro Satomi, M.D.; Yuki Shinya, M.D.; Ryota Nakamura, M.D.; Motoi Takahashi, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2023)
Purpose: This study aims to examine the clinical autologous osteochondral grafts (AOG) outcomes for knee osteochondral diseases at operative ages >60 years, and to determine whether patients are able to sit straight in Japanese style after AOG. Methods: All patients who underwent AOG for knee osteochondral diseases between November 2001 and April 2018 were retrospectively identified. The inclusion criteria were AOG only without osteotomy, operative ages between 60 and 79 years, >2 years of follow-up, and involved femorotibial angle between 169° and 179° (normal alignment). Patients who underwent osteotomy to improve knee alignment and patients with inflammatory diseases such as rheumatoid arthritis were excluded. The patients’ knee symptoms and their clinical outcome were evaluated according to the criteria of the knee scoring system of the Japanese Orthopedic Association (JOA), International Knee Documentation Committee (IKDC) subjective score, and the ability of straight sitting in Japanese style. Results: This study enrolled 57 cases and 60 knee joints during the study period. The follow-up ratio was 85.1%. Moreover, 14 men and 43 women and 29 right and 31 left knee joints were included in this study. The mean operative age and mean follow-up period were 67.8 years (range 60-76 years) and 81.1 months (range 24-167 months), respectively. In addition, the study involved 30 cases and 32 knee joints (60s group), and 27 cases and 28 knee joints (70s group). Moreover, 34 cases and 36 knee joints had osteonecrosis (ON group), and 23 cases and 24 knee joints had cartilage injury (CI group). The IKDC subjective and JOA scores in both the 60s and 70s groups showed significant differences: 2 years after AOG ＞at the follow-up period, ＞at the preoperative period. The scores in both the CI and ON groups showed similar significant differences. Furthermore, 8.3% and 53.5% of the patients could sit straight in Japanese style at the preoperative period and 2 years after AOG, respectively. Conclusion: Even if the patient’s operative age was >60 years, the AOG only for their knee osteochondral diseases had good clinical outcomes, including the ability to sit straight in Japanese style. Level of Evidence: IV, Therapeutic case series Key words: autologous osteochondral grafts, aged patients, clinical outcome, knee joint, straight sitting in Japanese style